(untitled) (Iranian Journal of Kidney Diseases, 2018)
Introduction. The forkhead box P3 (FOXP3) gene is important for regulation and development of T cells, which are mediators of kidney allograft rejection. The FOXP3 gene polymorphism may be associated with the rejection of kidney transplants. This study was designed to determine the association of FOXP3 polymorphism with kidney transplant rejection. Materials and Methods. A total of 118 kidney transplant patients were included in this study and were grouped into rejection (n = 31) and nonrejection (n = 87) groups. The FOXP3 rs3761548 gene was genotyped by polymerase chain reaction-restriction fragment length polymorphism using the taqman probe technique. Gene polymorphism at rs3761548 of the FOXP3 gene was analyzed for association with rejection episodes and graft outcome of kidney transplants. Results. The CC genotype of rs3761548 was not present neither of the study nor the control group. The AA genotype was association with a higher risk of rejection compared to the C/A genotype (odds ratio, 2.329; 95% confidence interval, 1.041 to 5.210). The C/A genotype was also associated with a better response to treatment for rejection (odds ratio, 6.667; 95% confidence interval, 1.319 to 33.707) and better posttransplant graft function (odd ratio, 5.833; 95% confidence interval, 1.727 to 19.704). Conclusions. Our findings suggested an association between rejection episodes, posttransplant graft function, and the FOXP3 rs 3761648 polymorphism. Determination of FOXP3 rs 3761648 C/A genotype might be helpful for the identification of recipients with a lower risk of rejection and better graft survival.